TikTok Usage Intensity and Social Interaction: A Study of KPI Students at UIN Mahmud Yunus Batusangkar - Azizah Hamid; Marhen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines the relationship between TikTok usage intensity and social interaction among Islamic Communication and Broadcasting (KPI) students at UIN Mahmud Yunus Batusangkar. Preliminary observations revealed that 100% of KPI students actively use TikTok, with 93.1% spending more than three hours daily and 95.8% reporting that TikTok usage disrupts their face-to-face social interaction. This study employed a quantitative correlational design with descriptive analysis. Using simple random sampling via Slovin's formula (10% margin of error), 74 respondents were drawn from 291 active KPI students. Data were collected through a four-point Likert scale questionnaire. Instrument validation via Pearson Product Moment correlation (n = 32; r-table = 0.349) yielded 9 valid items for Variable X and 19 valid items for Variable Y, with Cronbach's Alpha of 0.807 and 0.924 respectively. As Kolmogorov-Smirnov normality testing confirmed non-normal data distribution (p = 0.035), Spearman's rank correlation was applied as the primary inferential test. TikTok usage intensity was categorized as high (Grand Mean = 3.12), and social interaction also as high (Grand Mean = 2.79). Hypothesis testing revealed a significant negative relationship between the two variables (r = −0.244; p = 0.036), indicating that higher TikTok usage intensity is associated with lower social interaction quality. This study recommends that students manage social media usage time wisely to preserve the quality of face-to-face social interaction.